ntegrating the intangible traditional forms of farming knowledge and practices of the Alur people of North-Western Uganda into the IP laws of Uganda - Gilbert, W (IOP Publishing Ltd, 2020)
Abstract. Documentation of traditional knowledge about traditional forms of farming knowledge and practices is essential to prevent its erosion over time, to enable its accessibility to subsequent generations of the same community, as well as other communities to attempt value-addition and possible benefit-sharing among various stakeholders, and finally to link innovation, investment and enterprise. Therefore, in the absence of documentation, potential investors and entrepreneurs would have to bear a very high transaction cost in order to seek information about potentially viable and useful IP produced by local communities and individual innovators. The transaction cost for a community to scout potential partners for value addition would even be higher. In such a situation, a single TK documentation could be beneficial. Accordingly, Integrating Intangible Traditional Farming Knowledge and practices in the IP laws of Uganda for global opportunities is a project intended to identify, collect, organize, register or record traditional forms of farming knowledge and practices (TK), as a means to dynamically maintain, manage, use, disseminate and or protect TK (positively or defensively). It is intended to form part of a comprehensive, thought-through the process of TK documentation and, in effect to act the documented knowledge would be shared only following the directions of the provider of knowledge. Unless authorized by the provider of knowledge, it will not be shared with anyone for any purpose and will be kept in the register as a confidential entry. However, broad categories of the knowledge or practices will be shared, so that interested seekers of this knowledge can be put in touch with providers.
Keywords: traditional forms, Alur people, IP laws.